Over 20 years of observations in the boreal forest reveal a decreasing trend of atmospheric new particle formation - Li, Xinyang; Li, Haiyan; Yao, Lei; Stolzenburg, Dominik; Sarnela, Nina; Vettikkat, Lejish; de Jonge, Robin Wollesen; Baalbaki, Rima; Uusitalo, Helmi; Kontkanen, Jenni; Lehtipalo, Katrianne; Daellenbach, Kaspar R.; et al. (Boreal Environment Research Publishing Board, 2024)
New particle formation (NPF) events substantially contribute to the number concentration of atmospheric particles and cloud condensation nuclei (CCN) which can further influence radiative balance and Earth's climate. Many short-term studies have found that sulfuric acid (H2SO4) and highly oxygenated organic molecules (HOM) are critical compounds in the early steps of NPF. However, it is not fully understood how NPF intensity and frequency respond to global warming and declining anthropogenic sulfur dioxide (SO2) emissions, affecting HOM and H2SO4 formation, respectively. Here, we report the results of long-term (over 20 years) datasets collected at the Station for Measuring Ecosystem-Atmosphere Relations (SMEAR) II (Hyytiälä, Finland). Owing to the significant contribution of HOM in the initial and subsequent particle formation and growth, we have derived a HOM proxy for conducting the long-term trend analysis. Measurement results together with modelled proxies reveal the declining trends of SO2, H2SO4, Condensation Sink (CS), NPF frequency and particle formation rate (J3) along with increasing trends of monoterpenes and HOM.